2015
DOI: 10.1364/oe.23.0a1194
|View full text |Cite
|
Sign up to set email alerts
|

Method of radial velocities for the estimation of aircraft wake vortex parameters from data measured by coherent Doppler lidar

Abstract: The method of radial velocities (RV) is applied to estimate aircraft wake vortex parameters from measurements conducted with pulsed coherent Doppler lidar (PCDL). Operations of the Stream Line lidar and the 2-µm PCDL are simulated numerically to analyze the accuracy of the estimated wake vortex parameters with the RV method. The RV method is also used to estimate wake vortex trajectories and circulation from lidar measurements at Tomsk and Munich airports. The method of velocity envelopes and the RV method are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 14 publications
(20 reference statements)
0
53
0
Order By: Relevance
“…using the method described in paper by Smalikho et al (2015c). Obtained values ε are rather small and decrease with height from 3 × 10 −5 m 2 s −13 at 200 m to approximately 10 −5 m 2 s −13 at 500 m. To calculate the contribution of the turbulence into variation of lidar estimates of the wind velocity, it is necessary to know, at least, the integral scale of the longitudinal wind velocity correlation L I .…”
Section: Observations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…using the method described in paper by Smalikho et al (2015c). Obtained values ε are rather small and decrease with height from 3 × 10 −5 m 2 s −13 at 200 m to approximately 10 −5 m 2 s −13 at 500 m. To calculate the contribution of the turbulence into variation of lidar estimates of the wind velocity, it is necessary to know, at least, the integral scale of the longitudinal wind velocity correlation L I .…”
Section: Observations and Analysismentioning
confidence: 99%
“…Studies of the gravity waves are carried out with the help of space images of the cloud fields in the visible and microwave regions (for example, German, 1985;Li et al, 2001) and radar images of the sea surface (for example, Spiridonov et al, 1987;Chunchuzov et al, 2000). Experimental investigations of AGWs in the ionosphere from the scattering of radio waves are carried out using different methods (for example, Benediktov et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The vortex circulation is obtained by fitting the velocity measured by LiDAR to that computed by the Burnham-Hallock vortex model. In the study conducted by Smalikho et al [79], the radial velocity method and the velocity envelope method showed similar performance in predicting the vortex position, while the error of vortex circulation estimated by the radial velocity method was 5 times higher. Computationally expensive methods that make use of estimators on spectrum-based analytical models are more accurate.…”
Section: Aircraft Wake Vortexmentioning
confidence: 88%
“…Many studies show the capabilities to track WV within the Doppler spectra and also within the radial wind data [5][6] [7]. In the past two years, WV algorithms have been developed based on the fitting of a WV theoretical model on radial wind speeds [7]. This method is used in the WINDCUBE WV characterization algorithm which detects, localizes and computes the circulation of WV.…”
Section: Wake Vortex Algorithms For Cdlsmentioning
confidence: 99%
“…This method is used in the WINDCUBE WV characterization algorithm which detects, localizes and computes the circulation of WV. This last step is performed by a least mean square optimization of a Hallock-Burnham WV theoretical model on the radial wind speeds, as proposed by Smalikho [7]. This algorithm has been validated on real wake vortex data collected at Paris-Charles-De-Gaulle airport in 2011 and at Toulouse-Blagnac airport in 2014 [9].…”
Section: Wake Vortex Algorithms For Cdlsmentioning
confidence: 99%